A REVIEW OF COMMERCIAL FINANCIAL INSTITUTIONS' PRIORITIES FOR SEVERAL INVESTMENT OPPORTUNITIES - ANIL DHASMANA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Investment contributes to a country's economic prosperity. Many people in India come from middleclass households and invest their money in a variety of investment options. These options are picked based on their requirements and preferences. The goal of this study is to assess retail investors' preferences on various investment possibilities as well as to explore the selection criteria used by retail investors, as well as to analyse risk and return perceptions and formulate ideas for establishing new channels. In this study, data was obtained by a structured questionnaire, with 240 responses received. According to the report, many investors invest for a consistent return, while others prefer hazardous investment options for wealth appreciation